The Implementation of School-Based Management in Supporting Standard of School Infrastructure and Facilities in Islamic Private School - Dina Destari; M. Saufi; Susi Arijanti; Gamar Al Haddar; Isna Kasmilawati (Departement of Mathematics Education, 2023)
This study aim to describe the efforts made in meeting the standards of facilities and infrastructure in implementing school-based management in an Islamic school in East Kalimantan. The research also describes community empowerment in the school environment and describes the supporting and inhibiting factors in implementing school-based management in meeting the standards of facilities and infrastructure. The place that the writer used as the research object was at one of the Islamic schools located in Samarinda, East Kalimantan. The time that the author uses to conduct research is from September 2022 to October 2022. In this look at the writer makes use of a descriptive qualitative approach, that is, a examine aimed at describing and studying phenomena, events, social sports, attitudes, ideals, perceptions, humans's mind in my opinion or in agencies. More than one descriptions are used to locate ideas and reasons that cause conclusions. Implementation of School-Based Management in Compliance with Infrastructure Standards in schools has been well managed and in accordance with the basic needs of schools regarding compliance with infrastructure standards.